2017
DOI: 10.7759/cureus.1378
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Scrambler Therapy for the Treatment of Chronic Post-Mastectomy Pain (cPMP)

Abstract: Chronic post-mastectomy pain (cPMP), including post-lumpectomy pain, is common with no established ways of treatment. We treated three consecutive patients referred with cPMP with scrambler therapy (ST), a non-invasive electrical neurocutaneous stimulation. Treatment was given across the area of pain following the dermatomes for 45 minutes daily, for several consecutive days until relief, and then was repeated as needed. The ST MC5A device synthesizes 16 different waveforms that resemble action potentials, del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
10
0
1
Order By: Relevance
“…11 This neuromodulatory therapy has been investigated for the treatment of persistent peripheral neuropathic pain, largely in open-label observational trials, in several conditions including chemotherapy-induced neuropathy, postherpetic neuralgia, and postsurgical neuropathic pain with promising results. [11][12][13][14][15][16][17] Patients report sustained relief after undergoing daily treatment sessions for 10 consecutive weekdays. 11 Anecdotal evidence supports Scrambler therapy for use in patients with persistent central neuropathic pain, 18,19 but no rigorous studies have systematically tested the benefit or sustainability of Scrambler vs a placebo treatment.…”
mentioning
confidence: 99%
“…11 This neuromodulatory therapy has been investigated for the treatment of persistent peripheral neuropathic pain, largely in open-label observational trials, in several conditions including chemotherapy-induced neuropathy, postherpetic neuralgia, and postsurgical neuropathic pain with promising results. [11][12][13][14][15][16][17] Patients report sustained relief after undergoing daily treatment sessions for 10 consecutive weekdays. 11 Anecdotal evidence supports Scrambler therapy for use in patients with persistent central neuropathic pain, 18,19 but no rigorous studies have systematically tested the benefit or sustainability of Scrambler vs a placebo treatment.…”
mentioning
confidence: 99%
“…Portanto, o impacto estético e mudança da rotina diária pode causar uma diminuição na qualidade de vida principalmente nos primeiros meses. 5,6,[22][23] Estudo que utilizou o questionário SF-36 apontou que mulheres que realizaram a cirurgia de quadrantectomia e não necessitaram de reconstrução mamária possuem os melhores escores médios em todos os domínios e, portanto, têm melhor qualidade de vida (QV), seguidas do grupo de mastectomizadas que fizeram reconstrução. O grupo de mulheres mastectomizadas que não fizeram a reconstrução tem um nível muito baixo de QV, seguido pelo grupo das mulheres que realizaram a quadrantectomia e também não fizeram a reconstrução.…”
Section: Discussionunclassified
“…Additionally, he read a full explanation of the study’s purpose and methods, and consented to this experiment. Investigational Review Board approval is not required if one or fewer cases are reported 7 ) . The study adhered to the principles of the Declaration of Helsinki.…”
Section: Subject and Methodsmentioning
confidence: 99%